Integration of aerobic granulation and UV/H2O2 processes in a continuous flow system for the degradation of sulfolane in contaminated water. Issue 6 (6th May 2020) - Khan, Muhammad Faizan; Yu, Linlong; Hollman, Jordan; Tay, Joo Hwa; Achari, Gopal
Abstract : Aerobic granulation and UV/H2 O2 in a continuous flow-through reactor can effectively degrade emerging contaminates, such as sulfolane. Abstract : Sulfolane contamination has increasingly become a major environmental concern around the world with emerging reports of groundwater, drinking water wells and soil contamination. In this study, a novel approach of integrating aerobic granulation technology with UV/H2 O2 process in a continuous flow-through operation sequence was investigated to remediate sulfolane contaminated waters. The new hybrid technology was able to eliminate more than 99.99% of sulfolane in less than 6.3 h of combined retention time. The degradation kinetics of sulfolane were evaluated in batch and continuous flow operation which showed zero and first order for aerobic granulation and UV/H2 O2 processes, respectively. In addition, the flow-through system was able to generate and maintain a healthy aerobic granular system characterized by a stable MLVSS/MLSS ratio as well as elemental and bacterial community compositions within the granules. H2 O2 concentration was a crucial element for sulfolane degradation in UV/H2 O2 process and various key factors were also identified that govern residual H2 O2 concentration in UV/H2 O2 effluents.